Infectious Diseases of North American Black Bears (Ursus americanus): Parasites (Part 2) - Zimmerman, D.; Mitchell, Mark (Wildlife Rehabilitation Bulletin, 2006)
Black bears (Ursus americanus) serve as an important keystone species within an ecosystem and can serve as sentinels for environmental health. Wildlife rehabilitators, biologists, and veterinarians working with these animals should familiarize themselves with infectious diseases commonly associated with these ursids. The purpose of this paper is to provide a literature review of the common endoparasites and ectoparasites associated with black bears.